Regeneration Enhances Metastasis: A Novel Role for Neurovascular Signaling in Promoting Melanoma Brain Metastasis - Prakash, Roshini; Izraely, Sivan; Thareja, Nikita S.; Lee, Rex H.; Rappaport, Maya; Kawaguchi, Riki; Sagi-Assif, Orit; Ben-Menachem, Shlomit; Meshel, Tsipi; Machnicki, Michal; Ohe, Shuichi; Hoon, Dave S.; et al. (Frontiers in Neuroscience, 2019)
Neural repair after stroke involves initiation of a cellular proliferative program in the form of angiogenesis, neurogenesis and molecular growth signals in the surrounding tissue elements. This cellular environment constitutes a niche ion which regeneration of blood new vessels and new neurons leads to partial tissue repair after stroke. Cancer metastasis has similar proliferative cellular events in the brain and other organs. Do cancer and CNS tissue repair share similar cellular processes? In this study, we identify a novel role of the regenerative neurovascular niche induced by stroke in promoting brain melanoma metastasis through enhancing cellular interactions with surrounding niche components. Repair-mediated neurovascular signaling induces metastatic cells to express genes crucial to metastasis. Mimicking stroke-like conditions in vitro displays an enhancement of metastatic migration potential and allows for the determination of cell-specific signals produced by the regenerative neurovascular niche. Comparative analysis of both in vitro and in vivo expression profiles reveals a major contribution of endothelial cells in mediating melanoma metastasis. These results point to a previously undiscovered role of the regenerative neurovascular niche in shaping the tumor microenvironment and brain metastatic landscape.